The structure of nematodes - Bird, Alan F. (Academic Press, 1991)
An expanded version of the first edition published in 1971, each section of this second edition has been updated and a new section on nematodes has been added. It is aimed at all workers interested in nematodes irrespective of whether they do research on nematodes that are parasites on animals or plants or free-living in the soil. Highlights include. Up-to-date literature review of the structures of all types of nematodes, both free living and parasitic. More than 100 photographs and illustrations. New chapter on the pathology of nematodes. Comparisons throughout between the two major groups of nematodes - the Secernentea and Andenophorea.